The effect of cerium dioxide nanocrystals on oxidative stress parametrs in irradiated human skin mesenchamal steam-embeded scaffolds - Kot, Yu; Kot, K.; Klochkov, V.; Yefimova, S.; Trufanova, N.; Petrenko, O.; Tkachenko, A.; Prokopiuk, V.Yu.; Onishchenko, A.; Kulik, M. (Abstract book of International Conference "Nanotechnologies and Nanomaterials"NANO-2022, 2022)
Cerium dioxide nanocrystals (CeO 2 ) are today one of the most promising classes of antioxidant materials. The aim of the study was to substantiate experimentally in vitro the possibility of using CeO 2 nanocrystals as an antioxidant for cell therapy of radiation burns. Spherical CeO 2 nanoparticles (D=1-2 nm) were synthesized in the Nanostructured Materials Department named by Yu.V. Malyukin of Institute for Scintillation Materials of NAS of Ukraine. The work was carried out on human skin mesenchymal stem cells-embedded scaffolds (hsMSCs-scaffolds). Cells subcultured until passage 3 (Eppendorf Galaxy 14S, 37°С, 5%СО 2 , 99% RH) with viability of 86% (Invitrogen Countess Counter) were then seeded on a highly porous 3D cell culture polystyrene scaffold (Alvetex Scaffold, 96 well, REPROCELL) and cultured for 10 days until the culture density of 84%. 1 hour prior to irradiation, a suspension of nanoparticles was added to the culture medium (αMEM + 10% FBS, Gibco) to a final concentration of 10, 20 and 40 nM), and incubated for 1 hour (Eppendorf Galaxy 14S, 37°С, 5% СО 2 , 99% RH). After replacing the medium with nanoparticles free one, the cells were irradiated on the gamma complex Rokus AM (Co 60 ). The dose of irradiation was 0.75 Gy (104kV, 9mA, 0.2 Gy/min, duration of irradiation – 225 sec). Two and six hours after irradiation, the fluorescence imaging (Olympus FV10iLIV confocal microscope, cellSense software), fluorimetric determination (Biotek FL600 reader, KC4 software) of the concentration of reactive oxygen species (ROS) (DCFDA, Ex/Em=495/529 nm), lipid hydroperoxides (MitoPeDPP, Ex/Em=452/470 nm), determination of the degree of DNA fragmentation by comet analysis (Mupid-exU System, Alpha Innotech Red™ Imaging System, CASPlab software), spectrophotometric determination (Biotek FL600 reader, KC4 software) of the enzymatic activity of superoxide dismutase and catalase (Abcam kits) were carried out in the hsMSCs - scaffolds. It was shown that in the absence of irradiation, nanoparticles at concentrations of 10 and 20 nM do not cause changes in the studied parameters. The concentration of the nanoparticles 40 nM caused a decrease in cell viability by 7% after 6 hours of cultivation on a background of absence of changes in other parameters. This concentration also proved to be ineffective for maintaining the vitality of cells after irradiation - the number of living cells decreased both in the presence and absence of nanoparticles after 6 hours of cultivation by 28%. Pre-incubation with nanoparticles at a concentration of 10 and 20 nM resulted in an increase in the number of living cells in culture 6 hours after irradiation by 11% and 17%, respectively, compared with irradiated cells non- preincubated with nanoparticles. In 2 and 6 hours after irradiation, the concentration of ROS and lipid hydroperoxides increased by 6.2 and 8.5 times, respectively, in the culture. The degree of fragmentation of nuclear DNA increased by 6.5 times. In this case, the activity of SOD and catalase decreased by 6 hours of observation for 3.6 and 5.8 times, respectively. Pre-incubation with CeO 2 nanoparticles at all used concentrations resulted in a significant decrease in prooxidant indices in irradiated culture. Herewith, the most prominent protective effect was provided by the concentration of 20 nM – for 6th hour of cultivation after irradiation, the concentration of ROS and lipid hydroperoxides was respectively 46% and 29% less, and the activity of SOD and catalase was 71% and 108% higher than in irradiated culture without nanoparticles. At the same time, regardless of the concentration of nanoparticles, the degree of DNA fragmentation remained at the level of irradiated cells without nanoparticles, which apparently is either a consequence of long-term effects of ROS overproduction or the inability to fix defects by cell repair systems over the past observation time. Thus, spherical nanoparticles CeO 2 (D=1-2 nm) at a concentration of 20 nM can be used in cell therapy of skin lesions to normalize the prooxidant-antioxidant balance. Acknowledgements. The authors express their gratitude to to the chief doctor Vasiliev L.Ya., to the doctor-radiologist Vasilyev L.L., and to the doctor- roentgenologist Trofimov A.V. for the consultations and for the provided technical possibility of irradiation on the basis of Grigoriev Institute for medical Radiology NAMS of Ukraine.
Keywords: nanoparticles; CeO 2; confocal microscope